Bovine Babesiosis in Turkey: Impact, Current Gaps, and Opportunities for Intervention - Ozubek, Sezayi; Bastos, Reginaldo G.; Alzan, Heba F.; Inci, Abdullah; Aktas, Munir; Suarez, Carlos E. (Mdpi, 2020)
Bovine babesiosis is a global tick-borne disease that causes important cattle losses and has potential zoonotic implications. The impact of bovine babesiosis in Turkey remains poorly characterized, but several Babesia spp., including B. bovis, B. bigemina, and B. divergens, among others and competent tick vectors, except Rhipicephalus microplus, have been recently identified in the country. Bovine babesiosis has been reported in all provinces but is more prevalent in central and highly humid areas in low and medium altitude regions of the country housing approximately 70% of the cattle population. Current control measures include acaricides and babesicidal drugs, but not live vaccines. Despite the perceived relevant impact of bovine babesiosis in Turkey, basic research programs focused on developing in vitro cultures of parasites, point-of-care diagnostic methods, vaccine development, omics analysis, and gene manipulation techniques of local Babesia strains are scarce. Additionally, no effective and coordinated control efforts managed by a central animal health authority have been established to date. Development of state-of-the-art research programs in bovine babesiosis to address current gaps in knowledge and implementation of long-term plans to control the disease will surely result in important economic, nutritional, and public health benefits for the country and the region.
Keywords: bovine babesiosis; Babesia; bovine; cattle; cattle industry in Turkey